Investigation on the electrical response behaviors of multiwalled carbon nanotube/polyurethane composite in organic solvent vapors - Shang, Songmin; Zeng, Wei; Tao, Xiao-ming (Sensors and actuators. B, Chemical, 2012)
A conducting composite was fabricated from the polyurethane (PU) filled with multiwalled carbon nanotubes (MWCNTs). In the organic vapors condition, the electric resistance of the composite exhibited a drastic increase when compared with its initial resistance. This is because of the matrix swelling induced by the solvent absorption that expands the gap between the fillers. We compared the electrical response behaviors with the organic vapor absorption behaviors of the composite. The non-Fickian (case II) diffusion theory was used to calculate the diffusion rate of organic vapor in the composite. The response rate equation of the composite depending on its organic vapor absorption behavior was then deduced. This equation is better able to explain the experimental phenomena of the selective sensitivity, the influence of vapor pressure and the test temperature. Furthermore, the experiment results showed that the Flory–Huggins interaction parameter and the acid–base interactions of the low permittivity of the organic vapors can determine the maximum magnitude of the response.